Adherence to antiretroviral therapy among HIV and AIDS patients at the Kwa-Thema Clinic in the Gauteng Province - Eyassu, Melaku Alazar (My University, 2015)
Background: The introduction of Antiretroviral Therapy (ART) has shown a tremendous reduction in HIV-related mortality and morbidity in people living with HIV / AIDS. Adherence to ART is the key to a successful treatment outcome. This study investigates the adherence of people living with HIV who are on ART. Since high levels of adherence of more than 95% are required to achieve effective suppression of the viral load, the researcher finds it very important to establish whether the people are pursuing what is expected of them. While the use of ART has brought much excitement and hope to both patients and medical practitioners in the world, it has also brought many new questions and challenges, including adherence issues. Adherence is, therefore, essential to achieve the success of ART. Aim: The main objective was to determine which factors influence adherence to ART among HIV and AIDS patients. Methods: This study utilised a quantitative cross-sectional descriptive design that was conducted at the Kwa-Thema Clinic, Ekurhuleni District, Gauteng Province. Data was collected using a structured questionnaire with open- and closed-ended questions where a total of 290 respondents were interviewed. Data was analysed using SPSS software version 22 and the analysed data was presented by means of charts, graphs, and frequency tables. Results: The findings indicated that the adherence to ART at the Kwa-Thema Clinic was 77%. Factors that were significantly associated with adherence were gender ((χ2 = 3.78, df = 1, p < 0.05).), level of education ((χ2 = 3.52, df = 3, p = 0.032), co-treatment of HIV and other infections (χ2 = 5.46, df = 4, p = 0.019).), ability to follow ART ((χ2 = 12.82, df = 1, p = 0.000 < 0.05), and types of ARV drugs. Recommendation: To enhance ART adherence the study recommends intensification of health education campaign against stigma and gender discrimination. Providing feedback to the patients by the healthcare providers regarding the benefits of ART is important. ix Conclusion: It was concluded that the adherence to ART at the Kwa-Thema Clinic was sub-optimal (less than 95%) at 77% but comparable to the adherence levels in other developing countries.
Thesis (MPH.) -- University of Limpopo, 2015
Keywords: Antiretroviral therapy; HIV / AIDS patients; 362.1969792; Highly active antiretroviral therapy; AIDS (Disease) Patients care -- Medical care; Patients compliance -- South Africa -- Gauteng